TEKNOLOGI TEPAT GUNA PEMANFAATAN SERBUK GERGAJI DAN PUPUK TINJA SEBAGAI CAMPURAN MEDIA TUMBUH BIBIT HUTAN TANAMAN RAKYAT - Deselina -; Efratenta KD; Bilman WS (DHARMA RAFLESIA, 2018)
The purpose of this community service activity is to produce qualified seeds of forest plants, reduce sawdust waste and human sewage, providing value-added sawdust and human sewage so that it becomes more useful, reducing the use of topsoil, thereby reducing topsoil dredging. This service activity was conducted in August to October 2014 at Pulau Beringin Village, District of Pondok Kelapa, Central Bengkulu. The targets of the activity are the members of farmers and members of the youth group. The activity uses methods of counseling, training and demonstration. Making the mixture media from sawdust and humanure for growing media of community plantation forest seedling in Pulau Beringin Village is one right step in the process of sawmill waste business and household waste. Making the growing medium mixture of these wastes in addition to add to the skills of the members of farmer groups and the youth institution in managing waste can also be used as an attempt to increase the income of members of farmers and members of the youth group in the village of Pulau Beringin. Keywords: sawdust, humanure, community plantation forest seedlings, Pulau Beringin